Secondary Vocational Education : International Experience - World Bank Group (World Bank, Washington, DC, 2016)
According to UNESCO, roughly 120 countries provide some form of technical or vocational secondary education, as distinct from a purely generalist curriculum. An overview of each administration’s secondary vocational education provision is given below under sub-headings suggested by the Terms of Reference (ToR) for this study. The information was gathered through a review of available literature. This varied from administration to administration both in terms of its coverage and of its quality. As a result, the information on each administration is somewhat diverse. This is particularly the case for objective evaluations of administrations’ systems. The report ends by posing nine questions for the Government of India to consider when planning the introduction of vocational education to secondary schools: (i) what is the place of school-based vocational education within India’s National Skills Qualification Framework? (ii) how much choice should be left to school students to decide on the balance of general and vocational education in their learning programme? (iii) what proportion of the vocational education curriculum should be devoted to general education? (iv) how can sufficient numbers of teachers of good quality be found to teach growing number of vocational students? (v) how beneficial is objective careers guidance for school pupils? (vi) what is the role or purpose of work experience for school pupils? (vii) what contribution to vocational education can be expected from employers if the labour market is largely informal with a small manufacturing sector? (viii) what form should assessment take, how would it be carried out and is there a relationship between it and general education? (ix) how can responsibility for vocational secondary education be allocated within a federal system of government? Finally, what should be clear from this study is that administrations develop policies and practices based on their history, their economic and geographic context and their vision, and that these policies will therefore vary between administrations.